Work capacity and cardiopulmonary adaptation of the obese subject during exercise testing. - Salvadori A; Fanari P; Mazza P; Agosti R; Longhini E; Salvadori, A; Fanari, P; Mazza, P; Agosti, R; Longhini, E (CHEST, 1992)
Twelve obese patients (six male subjects) aged 17 to 42 years with a mean body mass index (BMI) of 40 kg/m2 and 12 normal subjects (six male subjects) aged 19 to 39 years with a mean BMI of 22 kg/m2 underwent a cycloergometric test until exhaustion to assess work capacity and cardiopulmonary adaptations of the two groups. Minute ventilation, expiratory gas concentrations, and heart rate, together with anaerobic threshold (AT) were determined in each subject during the test. The same subjects were then submitted to normocapnic hyperpnea at rest to assess the oxygen cost of breathing. We found that in the obese patients, the maximal sustainable work rate was not different from that of controls (120 vs 136 W) while AT was significantly lower (78 vs 110 W). Nevertheless, there was no difference in maximum VO2 and in VO2 at AT levels (expressed in milliliters per minute) indicating that cardiac, pulmonary, vascular, and muscle performance did not differ from obese to normal subjects. Greater muscular effort was needed by obese patients when moving their heavier legs and less when doing external work with a decreased gross mechanical efficiency and an identical net mechanical efficiency between the two groups.